Juan Díaz de Solís and the Discovery of the Río de la Plata. Transnational Dialogues and Discussions for the Elaboration of an Official Historical Narrative in the Southern Cone (1860-1900) (2023)
This article examines the process of construction of the official historical narrative around the figure of the sailor Juan Díaz de Solís during the second half of the nineteenth century. The analysis of the dialogues and controversies that took place between different actors in the literate community at the regional level (Southern Cone) aims to reveal the different ways of interpreting the past and the heterogeneous strategies used to present them to public opinion, as well as to understand how these exchanges placed the manner in which the practice of the historical discipline itself was conceived at the center of the debate. In this way, the functioning of complex intellectual networks that served for the circulation of historical knowledge and the elaboration of discourses that attempted to elucidate this and other events related to the American colonial past is exposed.